(untitled) (Research, Society and Development, 2025)
Annual ryegrass is one of the main cool-season forage crops in southern Brazil, but seed quality has compromised its performance. Studies indicate that around 90% of the ryegrass seeds sold in Brazil do not meet minimum quality standards. This affects pasture performance and subsequent crops, with impacts such as low straw yield, pests, and diseases. Although germination and seed weight are useful parameters for assessing seed quality, there are no legal guarantees regarding seed vigor. The objective of this study was to analyze the relationship between germination, thousand-seed weight, and seed vigor of ryegrass through a review of 26 studies using a literature review. The results showed significant positive correlations between germination and vigor variables, such as first germination count, germination speed index, and accelerated aging. The study also indicated that seeds weighing more than 1.80g showed better germination, suggesting higher physiological quality. The study concludes that to ensure successful ryegrass establishment, it is essential to invest in high-germination seeds, as they are directly related to vigor and the ability to overcome adverse conditions. Choosing high-quality seeds can lead to better performance in pastures and livestock production systems.